UNVEILING THE IMPACT OF BRAND IDENTITY TOWARDS BRAND ADVOCACY (CASE STUDY: SOMETHINC) - Hansopaheluwakan, Scherly; Hayanimasy, Ratu Allysa; Vannessa, Vannessa (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study seeks to examine the impact of Brand Ambassador, Brand Credibility, and Brand Love on Brand Advocacy within the cosmetics industry, with a particular focus on Somethinc serums. Using quantitative methods, data was collected from those aged 18-34 years who had previously purchased and used serum from Somethinc. The sampling technique used Hair theory where data was collected from 110 respondents with an observation period of two months which took place in January-March. The analytical techniques employed in this research encompass construct reliability and validity tests, inner model tests, and hypothesis tests, facilitated by SmartPLS 4.1.0.1 software. The results of this research show that 2 (two) variables, Brand Ambassador and Brand Credibility, have a positive and significant influence on Brand Advocacy. Meanwhile, the Brand Love variable does not have a positive and significant influence on Brand Advocacy with the bootstrapping test results obtaining a p-value of 0.440.